Elaboração de estratégia de marketing de conteúdo para o Instituto Brasileiro de Ecopsicologia e sua biblioteca digital - Chitacumula, Alice de Carvalho (Universidade Federal de São Carlos, 2023)
This research investigates the development of content marketing strategies in an information unit, seeking to understand their viability for promoting services and the site's authority in the digital world. Content marketing has been highlighted as an approach to strengthening the relationship between organizations and their target audience. In the context of information units, which include libraries, documentation centers and information services, the adoption of content marketing strategies offers the opportunity to optimize communication, disseminate relevant information and attract new users. The research employs a methodology that involves a qualitative, applied and exploratory analysis. It also manifests methodological procedures with bibliographical, documentary, field research, case study and action research characteristics. Initially, a literature review was carried out to map out the main concepts related to this area of activity. This was followed by a study of the digital landscape of the Brazilian Ecopsychology Institute (IBE) and the Ecopsychology Digital Library (BDE) to understand how and if this digital marketing strategy could be implemented.
Development of a content marketing strategy for the Brazilian Institute of Ecopsychology and its digital library
Keywords: Marketing digital; Marketing de conteúdo; Unidades de informação; Instituto Brasileiro de Ecopsicologia; Biblioteca Digital de Ecopsicologia; Digital marketing; Content marketing; Information units; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA::PROCESSOS DE DISSEMINACAO DA INFORMACAO; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA::TECNICAS DE RECUPERACAO DE INFORMACAO